Clinical Reasoning in Nursing Students - Darvishi Alamouti, Hadi; Nikravan Mofrad, Malahat; Borzabadi Farahani, Ziba; Amini, Amin Reza (Advances in Nursing & Midwifery, 2021)
Abstract Introduction: Diagnosis and understanding of patient conditions require nurses 'clinical reasoning skills, as in the absence of this skill; the nurses will not be able to diagnose the patients' condition and will impose harmful consequences on the patient. The purpose of this study is to evaluate and compare the clinical reasoning skills of the nursing students at Shahid Beheshti University of Medical Sciences at the end of theoretical courses in medical-surgical nursing in 2018. Methods: In this descriptive-comparative study, 150 nursing students from freshmen, sophomores, and juniors studying at the Faculty of Nursing and Midwifery of Shahid Beheshti University of Medical Sciences were selected by stratified sampling method. Students in each year comprised one category and the total number of was 3, also the number of students per category was 50, and the total number of categories will be equal to 9. Data were collected using a researcher-made questionnaire employing Key Feature Problem (KFP) method and analyzed using descriptive statistics by SPSS V.20 software. Results: The results showed that there is a significant difference between the grades of third-year students and those in their first and second years of study (P <0.001). Based on the results, the clinical reasoning skill in the first year was poor (51.59 ± 0.06%), in the second year was very weak (48.41 ± 0.09%) and in third-year students was very weak (37.62 ± 0.88). Also, the average skill of clinical reasoning of all students was very weak with a mean percentage of 46.01%. Conclusions: The findings indicate that the level of students' clinical reasoning skills has been declined comparatively from freshmen to juniors. In general, the level of clinical skills in nursing students of Shahid Beheshti University of Medical Sciences is disappointingly low.